MALATYA BÖLGESİNDE YETİŞTİRİLEN SIĞIRLARDA PARAİNFLUENZAVİRUS TİP-3 ENFEKSİYONU ÜZERİNE SEROEPİDEMİYOLOJİK ARAŞTIRMA - ÖZDARENDELİ, AYKUT (Fırat Üniveristesi, 1997)
Hemaglutinasyon inhibisyon ( HI ) testi kullanılarak sığır serum numuneleri Parainfluenza tip-3 ( PI-3 ) virusuna karşı antikor varlığı bakımından kontrol edildi. Serum numuneleri sonbahar 1994 ve onu izleyen ilkbaharda Malatya'da klinik olarak sağlıklı sığırlardan alındı. Kontrol edilen 1000 sığır serumlarından 897'sinde (%89,7 ) PI-3 virusuna karşı reziprokal antikor titreleri 1:16'dan 1:1024'e kadar değişti, ilkbaharda sığırlarda tesbit edilen seropozitiflerin oranı sonbahardakilerden yüksek bulundu.

Serological Survey for Hemaggglutination-lnhibition Antibodies to Parainfluenzavirus Type 3 (PI-3 ) in Cattle in Malatya and its Vicinity. Cattle serum samples were examined for the antibodies against parainfluenzavirus type 3 virus using the hemaglutination-inhibition (HI) test. These sera were collected in autumn 1994 and in it's following spring from clinically healty cattle in Malatya. Antibodies to PI-3 virus were detected in 897 of 1000 cattle sera (%89,7). Resiprocal antibody titreş to PI-3 virus in cattle ranged from 1:16 to 1:1024. It was found that the proportion of seropositif sera determined in cattle in spring was higher than those in autumn.
Serological survey for hemagglutination-inhibition antibodies to parainfluenzavirus type 3(PI-3) in cattle in Malatya and its vicinity
Keywords: Veteriner Hekimliği; Veterinary Medicine